2018
DOI: 10.1093/nutrit/nuy010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of resveratrol supplementation on cognitive performance and mood in adults: a systematic literature review and meta-analysis of randomized controlled trials

Abstract: The results of this review indicate that resveratrol supplementation might improve select measures of cognitive performance; however, the current literature is inconsistent and limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 39 publications
3
40
0
Order By: Relevance
“…However, results of resveratrol supplementation in human are inconsistent. A meta-analysis of randomized controlled trials suggests that resveratrol may be beneficial (Marx et al, 2018) or may have no significant impact on the selected measures of cognitive performance (Farzaei et al, 2018). Several neuroprotective properties of resveratrol have been suggested in the studies of its effects in the intracerebral hemorrhage (Bonsack et al, 2017), cerebral neurodamage (Nalagoni & Karnati, 2016), and central nervous system injuries such as stroke .…”
Section: Neuroprotectionmentioning
confidence: 99%
“…However, results of resveratrol supplementation in human are inconsistent. A meta-analysis of randomized controlled trials suggests that resveratrol may be beneficial (Marx et al, 2018) or may have no significant impact on the selected measures of cognitive performance (Farzaei et al, 2018). Several neuroprotective properties of resveratrol have been suggested in the studies of its effects in the intracerebral hemorrhage (Bonsack et al, 2017), cerebral neurodamage (Nalagoni & Karnati, 2016), and central nervous system injuries such as stroke .…”
Section: Neuroprotectionmentioning
confidence: 99%
“…While no improvement in verbal memory was observed in elderly people after receiving RSV [46], the consumption of RSV enhances both cerebrovascular function and cognition in postmenopausal women [48]. In addition, meta-analysis [50] considers that RSV has no significant effect on memory improvement or cognitive performance. The possible reasons for these discrepancies could be due to variations in the protocol of RSV administration and the patient status.…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Consumption of two of those capsules (150 mg) for 14 weeks enhances both cerebrovascular function and cognition in postmenopausal women aged 45-85 years [48]. In contrast, recent systematic reviews and meta-analysis, which included only clinical studies, RSV has no significant effect on memory improvement or cognitive performance as well as mood state [49,50]. A summary of the RSV preventive effects during elderly is shown in Figure 1.…”
Section: Resveratrol As a Possible Protective Agent Of Brain Aging: Ementioning
confidence: 99%
“…In contrast, Wightman et al [ 82 ] demonstrated a lack of any interpretable cognitive effects of 28 days’ supplementation with 500 mg resveratrol, although subjective fatigue was reduced. A recent meta-analysis reported beneficial effects of resveratrol on cognitive function [ 90 ]. However, only three studies out of the ten that were included in the analysis reported benefits, and two of these three studies administered resveratrol alongside other polyphenols (red wine and quercetin, respectively).…”
Section: Phenolicsmentioning
confidence: 99%